Pengaruh Penggunaan Metode Kerja Kelompok Terhadap Hasil Belajar Pendidikan Agama Kristen Dan Budi Pekerti Peserta Didik Kelas VIII Semester Ganjil Di SMP Negeri 4 Balige Tahun Pelajaran 2023/2024 - Lestari Hutahaean; Hasudungan Simatupang; Marudut Situmorang; Dorlan Naibaho; Lince R.T Simamora; Malani Simanungkalit (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2023)
The aim of this research is to determine the positive and significant influence of using group work methods on the learning outcomes of Christian Religious Education and Character Education for class VIII odd semester students at SMP Negeri 4 Balige for the 2023/2024 academic year. The method used in this research uses quantitative methods with descriptive and inferential approaches. The population is all class VIII odd semester students at SMP Negeri 4 Balige for the 2023/2024 academic year who are Protestant Christians totaling 208 people and the sample was determined to be 42 people, namely 20% of the total population. Data was collected using positive closed items with 23 questionnaire items for variable odd semester at SMP Negeri 4 Balige Academic Year 2023/2024: 1) Test analysis requirements: a) positive relationship test obtained value rxy = 0.460 > rtable(a=0.05,n=42) = 0.304 thus it is known that there is positive relationship between variable variable Y. c) Regression coefficient of determination test (r2) = 21.2%. 2) Influence test: Regression equation test, obtained the regression equation Y ̂=